2018
DOI: 10.5114/ada.2018.77663
|View full text |Cite
|
Sign up to set email alerts
|

Antigen recognition in the pathogenesis of immunoglobulin A-related autoimmune bullous diseases

Abstract: Immunoglobulin A (IgA) is the most common subtype of antibodies in mucosal surfaces. In most of autoimmune bullous diseases, however, immunoglobulin G (IgG) is the main pathogenic antibody that plays a role through complementation. The IgA antibody for epidermal connection protein can be found in the sera of some patients with blistering skin disease. Of these patients, some have the IgA antibody in their sera, while others have IgG and IgA antibodies. IgA-related autoimmune bullous diseases are less common in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…However, many patients exhibit atypical clinical manifestations and thus their conditions are difficult to categorize into BP or LABD. 6 We diagnosed these three cases as LAGBD by histopathological and immunological results. The three patients showed subepidermal blisters with predominantly neutrophilic infiltrates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, many patients exhibit atypical clinical manifestations and thus their conditions are difficult to categorize into BP or LABD. 6 We diagnosed these three cases as LAGBD by histopathological and immunological results. The three patients showed subepidermal blisters with predominantly neutrophilic infiltrates.…”
Section: Discussionmentioning
confidence: 99%
“…Their studies also showed the sensitivity of ELISAs for IgA and IgG antibodies in LABD was lower than ss‐IIF. Similar to LABD, LAGBD has been reported to have IgA and IgG binding mostly to the epidermal surface and rarely combined epidermal‐dermal or dermal sites 4–8 …”
Section: Discussionmentioning
confidence: 99%
“…The relationship between LAGBD clinical manifestations and the type of predominant antibody highlights that BP, LAGBD, and LABD are on a spectrum. 20 …”
Section: Discussionmentioning
confidence: 99%
“…The relationship between LAGBD clinical manifestations and the type of predominant antibody highlights that BP, LAGBD, and LABD are on a spectrum. 20 Histopathologic evaluation shows subepidermal bullae. 1 Eosinophilic spongiosis and/or dermal infiltrate of eosinophils are seen in BP.…”
Section: Discussionmentioning
confidence: 99%
“…Both LABD and LAGBD are blistering diseases caused by deposition of autoantibodies targeting integral components of BMZ, similar to BP. BP, LAGBD, and LABD are believed to be on a spectrum, and for LAGBD, the clinical presentation and pathological findings are determined by predominance of either IgG or IgA deposited along the BMZ [ 55 ]. In LABD, the IgA autoantibodies are formed against the 97 kDa or 120 kDa fractions of BP180, and sometimes collagen VII (COL7) [ 36 ].…”
Section: Autoimmune Diseases Of the Skinmentioning
confidence: 99%